Protection Of Indonesian Migrant Workers' Children In Bilah Barat: Perspectives Of Positive Law And Islamic Law - Siti Jamroh Rambe; Uswatun Hasanah (Universitas Ibn Khaldun, 2026)
The phenomenon of Indonesian migrant workers has created social consequences for children left behind, particularly in caregiving, education, emotional communication, and social protection. This article examines the protection of Indonesian migrant workers' children in Bilah Barat District, Labuhanbatu Regency, from the perspective of positive law and Islamic law. This study employs an empirical legal method, drawing on statutory, case, sociological, and Islamic legal approaches. Primary data were obtained through in-depth interviews with 18 informants from five migrant-worker families, along with one supporting informant, the Head of the Religious Affairs Office, and one village official. Within each family, the child, substitute caregiver, and migrant-worker parent were interviewed to allow within-family triangulation. Secondary data were collected from legislation, classical fiqh books, and relevant scientific literature. The research was conducted with ethical safeguards for child informants, including guardian consent, child assent, and the use of pseudonyms for all minors and their families to protect their identity. The findings show that child protection has a strong normative basis under Law Number 35 of 2014 on Child Protection and the Islamic legal concepts of hadhanah and maintenance. However, its implementation remains partial. The children of migrant workers experience non-ideal substitute care, emotional deprivation, educational vulnerability, misuse of remittance channels, and social risks, including child-marriage vulnerability. From an Islamic legal perspective, neglect of caregiving, maintenance, and protection may be categorized as tafrith, although the degree of fault varies depending on whether the failure stems from a parent's own dereliction or from an intervening third-party wrongdoing. This study argues that child protection for migrant-worker families requires stronger village data collection, integrated policy, school-based early detection, safe remittance mechanisms, and the involvement of religious institutions based on maqasid sharia. Keywords: child protection; hadhanah; Indonesian migrant workers; Islamic law; positive law.